Design of An Interactive Module for Historical Building Learning Using Board Game Puzzle Based On Multi-Marker Augmented Reality - Prasetyo aji, Pujo; Tolle, Herman; Sakti Pramukantoro, Eko (Faculty of Computer Science (FILKOM) Brawijaya University, 2023)
Augmented Reality (AR) technology is one of the new technologies that can display the virtual world into the real word. Augmented reality technology is widely applied into the educational field to help the learning process by representating an object in more realistic and detailed way. However, most of the implementations that carried out only using AR to show up an object from a single marker, even though there are still many ways on using AR functions to represent an information in more detailed and intersting ways. This study aims to develop a learning media to introduce histrorical building spesifically Indonesian Temple’s using multi-marker augmented reality. This study used ADDIE Model to develop suitable media for learning process. Based on the results of expert testing, the developed media obtained an avarage score 3,76 for media evaluation and 3,84 for material evaluation, which means the developed media was very feasible as a learning medium. Therefore, through this research we expect to provide a recommendation for AR application models using multi-marker AR method, futhermore the modules developed are intended to become information resource and learning material about historical building especially temples in Indonesia.